Ecoepidemiologia da Leishmania ssp em zona endêmica do Distrito do Tirirical - Rocha, Alessandra Lima (2013)
Leishmaniasis is a zoonosis which notification is mandatory in Brazil. São Luis Municipality is one Brazilian capitals where visceral leishmaniasis is endemic urban. This study was conducted in the District of Tirirical, district of São Raimundo, São Luis-MA which we evaluated the occurence of sandflies and seroprevalence of canine visceral leishmaniasis (CVL) as well as we investigated the role of marsupials in the epidemiological chain. The entomological survey showed that sandflies 4480 were captures, which belonged to nine species. Among them Lutzomya longipalpis was the specie more frequent. In regard the dogs survey was observed that among 341 dogs, 173 (50.73%) had anti- Leishmania sp, 135 (39.59%) were seronegative and 33 (9.67%) of the dogs had indeterminate results by ELISA/S7 test. The capture of marsupials was performed in 19 points and 12 captured animals were identified with Didelphis marsupialis. In serologic test (IFAT), and histological bone marrow smear was not detected the presence of the parasite. However, on examination of the Polymerase Chain Reaction (PCR) were detected DNA parasites the blood and bone marrow in 3 (25%) of the animals studied. These data indicate that marsupials could be a sylvatic reservoir of leishmaniasis in the state of Maranhão as it observed in Bahia State. Thus, we need to conduct other studies in order to elucidate the actual participation of D. marsupialis in the transmission cycle of this zoonosis in São Luís Municipality.